Kuwait Driving Cycle Generation Using Micro-Trip Combination Optimization Method Based on WLTC - Murat Otkur; Mohammad Doust (International Journal of Automotive Engineering, 2023)
ABSTRACT: Albeit the low population of Kuwait (World Ranking 129), vehicle ownership percentage is the highest in the Gulf Cooperation Council (GCC) countries and 29th in world raking. Therefore, transport vehicle emissions effect is importantly high and must be taken into consideration in order to fight with the Global Warming and pollution effects. For Internal Combustion Engine (ICE) propelled vehicles, generated emissions strongly depend on the driving profile. Despite the low surface area of Kuwait, percentage of dessert areas with no / limited road infrastructure is significantly high resulting to extreme traffic jam conditions especially in the Capital Governate (Kuwait City). Considering the peculiar traffic conditions in Kuwait, in order to make valuable emissions analysis research, there is a clear need for driving cycle generation for Kuwait. Within this study, more than 1200 km of data is measured using Matlab Mobile in 3 different vehicles and analyzed using Matlab software. Kuwait driving cycle is generated employing Worldwide Harmonized Light Vehicles Test Cycle (WLTC), based on targeting to achieve similar vehicle speed vs acceleration profiles via making vehicle speed scaling for each phase of the WLTC. Total length of the cycle is kept constant. Generated Kuwait driving cycle profile can be used for emissions and fuel economy analysis as a future work.